2021
DOI: 10.3389/fcell.2021.662754
|View full text |Cite
|
Sign up to set email alerts
|

Between Fate Choice and Self-Renewal—Heterogeneity of Adult Neural Crest-Derived Stem Cells

Abstract: Stem cells of the neural crest (NC) vitally participate to embryonic development, but also remain in distinct niches as quiescent neural crest-derived stem cell (NCSC) pools into adulthood. Although NCSC-populations share a high capacity for self-renewal and differentiation resulting in promising preclinical applications within the last two decades, inter- and intrapopulational differences exist in terms of their expression signatures and regenerative capability. Differentiation and self-renewal of stem cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 186 publications
1
23
0
Order By: Relevance
“…A following RT-PCR analysis revealed the presence of transcripts for GAPDH, eEF2 and Vimentin in the ten-cells-sample as well as in all three single cell approaches (Figure 1 E). Further transcriptional profiling revealed the heterogenous expression of the NCSC-markers S100, Snail and Twist, the latter being key players in EMT and highly important in the determination of NCSC-fate (reviewed in 2 ). In particular, S100 gene expression was detectable in the 10-cell-sample and in two out of three single-cell-samples.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A following RT-PCR analysis revealed the presence of transcripts for GAPDH, eEF2 and Vimentin in the ten-cells-sample as well as in all three single cell approaches (Figure 1 E). Further transcriptional profiling revealed the heterogenous expression of the NCSC-markers S100, Snail and Twist, the latter being key players in EMT and highly important in the determination of NCSC-fate (reviewed in 2 ). In particular, S100 gene expression was detectable in the 10-cell-sample and in two out of three single-cell-samples.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance to our findings, a range of studies reported intrapopulational variations of NCSCs, namely between clonally grown NCSC-cultures from the same population. The NCSC-clones were shown to strongly vary in their differentiation potential and molecular profile (reviewed in 2 ). In particular, Singhatanadgit and coworkers reported a highly heterogeneous differentiation potential between clonal human periodontal ligament stem cell cultures, which varied from sole osteogenic to multilineage differentiation 33 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations